The Misdiagnosis of CIDP: A Review - Jeffrey A. Allen (Neurology and Therapy, 2020)
Abstract There is a growing realization that many patients are incorrectly diagnosed with chronic inflammatory demyelinating polyneuropathy (CIDP), with at least half of patients that carry a diagnosis of CIDP in the USA possibly having a different explanation for their neuropathy or having no neuropathy at all. Many misdiagnosed patients go on to receive costly and potentially harmful treatments for a disease that they do not have, while at the same time missing an opportunity to treat their true ailment. The cost of misdiagnosis on patients and society is not trivial. Many factors contribute to misdiagnosis. Particular points of vulnerability include the evaluation of “atypical” CIDP, interpretation of equivocal nerve conduction studies, over-reliance on elevations in cerebrospinal fluid protein concentration in indeterminate ranges, and placing excessive diagnostic weight on subjective changes following the initiation of immunotherapy. In addition to heighted awareness of the challenges, adherence to CIDP diagnostic guidelines, utilization of objective metrics to document clinical change, and referrals to CIDP centers of excellence are strategies that may improve diagnostic accuracy.